Implementation Of Good Corporate Governance (Gcg) And Profit-Sharing Financing On Profitability In Sharia Commercial Banks - Sri Lestari Kurniawati; Zubaidah nasution (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2021)
This study aims to determine the effect of Good Corporate Governance and profit-sharing financing on the performance of sharia commercial banks in Indonesia as measured by profitability. This study is quantitative by using Profitability variables (ROA and ROE) as the dependent variable and Good Corporate Governance and profit-sharing financing (mudharabah, musyarakah) as independent variables. The purposive sampling was used as the sampling method in order to obtain 10 Sharia Commercial Banks (SCB) with a study period of 2009-2018. The analysis technique used is descriptive analysis and statistical analysis of panel data with eviews 8.0. The results of the study stated that Good Corporate Governance and mudhorobah profit-sharing had a significant positive effect on profitability (ROA and ROE).